Effectiveness of Pelvic Floor Muscle Training on Quality of Life in Women with Urinary Incontinence: A Systematic Review and Meta-Analysis - César Adrián Curillo-Aguirre; Enrique Gea-Izquierdo (Medicina, 2023)
Background and Objectives: Urinary incontinence (UI) is a condition that is more common in women than men and has an increasing prevalence with age. It provides a range of psychological and physical burdens that negatively affect the patient’s quality of life (QoL). However, the economic burden for the healthcare system is being augmented due to the increasing life expectancy of the population. This article aims to identify the effectiveness of pelvic floor muscle training (PFMT) on the QoL in women with UI. Materials and Methods: A systematic review and meta-analysis were conducted in the PubMed, EMBASE, ProQuest medicine, Cochrane Library, and Google Scholar databases. The terms selected according to components of PICOS were women with urinary incontinence, pelvic floor muscle training, watchful or other types of therapies, quality of life, randomized controlled trials, and interventional or observational studies. The articles included were those published between November 2018 and November 2022. Ten articles were found for the systematic review and eight for the meta-analysis. Results: The QoL moderately increased when PFMT was used on women with UI, the results indicating an overall small effect on the QoL across the controlled studies and a moderate effect on the QoL across the one-group pre-post-studies. Conclusions: Specific QoL domains, such as social activities and general health, also demonstrated benefits from PFMT interventions. This study confirmed the effectiveness of PFMT on the QoL in women with UI, mainly for patients with stress urinary incontinence.